1994
DOI: 10.1111/j.1467-9906.1994.tb00327.x
|View full text |Cite
|
Sign up to set email alerts
|

Sport and Downtown Development Strategy If You Build It, Will Jobs Come?

Abstract: Many policy analysts have cautioned against public spending for professional and amateur sports. Within the last year, numerous cities have received demands from major and minor league teams for investments. n e s e investments by the public sector can involve hundreds of millions of dollars and are usually ddended by the economic impact of the facilities or teams and the economic development and revitalization which will follow. Indianapolis formulated an economic development strategy which relied substantial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0
3

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(69 citation statements)
references
References 10 publications
1
65
0
3
Order By: Relevance
“…Moreover, while the construction phase may generate some employment, long term employment related to sport facilities is likely to be part-time, casual, low skilled, and low waged, thus not contributing in the improvement of the quality of full-time jobs (Baade, 1996;Hall, 2006;Whitson and Horne, 2006). Given these facts it is not surprising that the evidence suggests that the development and construction of stadiums does not generate a net addition to economic activity (Baade and Dye, 1990;Rosentraub, 1994;Crompton, 1995;Baade, 1996;Coates and Humphreys, 1999;Lertwachara and Cochran, 2007).…”
Section: Economic Impact Of Sports Eventsmentioning
confidence: 99%
“…Moreover, while the construction phase may generate some employment, long term employment related to sport facilities is likely to be part-time, casual, low skilled, and low waged, thus not contributing in the improvement of the quality of full-time jobs (Baade, 1996;Hall, 2006;Whitson and Horne, 2006). Given these facts it is not surprising that the evidence suggests that the development and construction of stadiums does not generate a net addition to economic activity (Baade and Dye, 1990;Rosentraub, 1994;Crompton, 1995;Baade, 1996;Coates and Humphreys, 1999;Lertwachara and Cochran, 2007).…”
Section: Economic Impact Of Sports Eventsmentioning
confidence: 99%
“…he also found that hotel occupancy rate and retail sales in a host city are not statistically increased during the Super Bowl compared to similar dates in non-Super Bowl years (Porter, 1999). Other studies indicate little evidence that hosting sporting events for the sake of community development with public subsidies provided significant positive economic impacts (hamilton & Kahn, 1997;rosentraub, 1994). Instead of economic gains, many cities that have hosted mega-sporting events have experienced a deficit after the events.…”
Section: Negative Externalitiesmentioning
confidence: 99%
“…With the exception of studies such as Meek (1997), which focused on sport-related economic activity at the national level in the US and Rosentraub, Swindell, Przybylski, and Mullins (1994), which evaluated the sport-related economic development strategy pursued by Indianapolis in the 1980s, the economic activity generated by both professional and amateur sports has received relatively little attention. While comparisons can be made between Rosentraub et al (1994) and the research undertaken in Sheffield, and these will be discussed later in the article, it is essentially the studies that have measured the economic importance of sport in various European countries that are most relevant to this research. Unlike much research in North America, with the exception of those aforementioned, the European literature tends to focus more holistically on measuring the contribution of all sporting activity to output and employment.…”
Section: Measuring the Economic Importance Of Sport: Previous Researchmentioning
confidence: 99%
“…As discussed earlier, little research has been carried out on the economic importance of sport in European cities therefore it is not possible to provide a comparative case study. However, a comparison can be made with Rosentraub et al (1994), which estimated the economic activity generated from sport in Indianapolis, a city that has like Sheffield, invested considerable resources into developing a sports strategy in response to a declining economy. Rosentraub et al (1994, p. 237) found that "…the entire impact of sports, under the best of circumstances, would amount to only 1.1% of the Indianapolis economy".…”
Section: Is Sheffield Really Bigger? the Importance Of The Commercialmentioning
confidence: 99%
See 1 more Smart Citation